Evaluasi Program Pembelajaran Jarak Jauh Pendidikan Agama Islam Pada Anak Buruh Migran Indonesia Di Sekolah Indonesia Kota Kinabalu, Malaysia - Prasetiyo, Nova Tri (Jurnal Administrasi Pendidikan Islam, 2024)
The Distance Learning Project is an instructive program that uses data and correspondence innovation (ICT) to work with the growing experience. This program expects to grow admittance to schooling for the offspring of Indonesian transient specialists in Sabah, who can't get training at Sekolah Indonesia Kota Kinabalu (SIKK) or through the Equivalency Schooling, especially in the subject of Islamic Strict Training. The primary school for PJJ program participants is SIKK. Using the CIPP (Context, Input, Process, Product) evaluation model, the purpose of this study is to evaluate the implementation of the Distance Learning Program in the Islamic Religious Education course at SIKK. An evaluation study approach is combined with a qualitative approach in the research. Qualitative conclusions are reached after data are gathered, classified, and interpreted. The assessment results demonstrate: a) Specific circumstance: The program is equipped for running in accordance with the school's vision and mission, however quality improvement is expected to accomplish the objectives completely. b) Information: More consideration is expected for the learning model or technique, costs, and other help to meet the goals. c) Interaction: Upgrades are required in learning innovation, intelligent materials, and correspondence media utilized. d) Item: The program results line up with the objectives, which are to improve the capacity and a chance for Indonesian traveler laborer kids to get to schooling.